Anaerobic treatment by a hybrid reactor - ÇALLI, BARIŞ (MARY ANN LIEBERT, INC, 2002)
Utilization or disposal of cheese whey is still one of the most significant problems in the dairy industry, even though there are a number of technological developments in the transformation of cheese whey to other useful products. In the last decade, parallel to the increase in the number of big cheese factories in Turkey, cheese whey generation in huge amounts has given rise to serious disposal problems. In this study, anaerobic treatability of a high strength acidic cheese whey taken from a middle-size cheese factory was investigated, which is treated aerobically together with cleaning and cooling waters in the existing treatment plant. The treatability study was carried out in a laboratory scale upflow hybrid bed reactor. The reactor showed a successful performance up to an organic loading rate of approximately 11 k-COD/m(3.)day and 2 days HRT with removal efficiencies more than 95% if the alkalinity in the reactor was stabilized by controlling the influent pH when necessary. Results of the anaerobic treatability indicated that the inefficient chemical oxygen demand (COD) removal, enormous foaming, and excessive sludge production problems faced by the existing aerobic treatment can be improved with a separate anaerobic unit prior to the aerobic stage.
Keywords: cheesemaking; cheese whey; anaerobic upflow hybrid bed reactor; inhibition; alkalinity deficiency; CHEESE-WHEY; WASTE-WATER